The Role of Fintech in Improving Financial Literacy in Micro Small to Medium Enterprises in Malang - Khalikussabir, Khalikussabir; Mawardi, Moh. Cholid; Handayati, Puji; Hermawan, Agus (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This journal aims to analyze the role of fintech in improving financial literacy in MSMEs in Malang. In this study, researchers took 3 samples randomly, from Malang Regency and Malang City. Analysis of the data used in this study is to use data reduction then data presentation and the last is conclusions. The results of the research are that of the four informants as a whole receiving well with the presence of fintech because fintech can facilitate transactions. Fintech also provides many benefits for MSMEs as well as more benefits from MSMEs. But of all the roles of fintech, the speakers in this study did not fully know what the role of fintech was because of the lack of socialization about fintech in MSMEs. The speaker said that in financing business capital still choose banks because banks are trusted and there are legal institutions that regulate them. Of the four speakers, the impact after using fintech is positive or there are many benefits to be gained after applying fintech to its business. The more efficient and effective business activities that make applied fintech and the development of the era require businesses to use fintech. Of the many advantages of fintech, there are certainly disadvantages, one of which is when the financial technology is problematic, it must be repaired and requires some time. Not only that, human resources that lack mastery of fintech make business people have to provide insight into fintech.